Assessing the biocementation of lateritic soil using hydraulic conductivity and bioinspired optimization approach - Roland Kufre Etim; Paul Yohanna; Adrian Oshioname Eberemu; Kolawole Juwonlo Osinubi; Thomas Stephen Ijimdiya (Scientific Reports)
Abstract The effectiveness of microbially induced calcite precipitation (MICP) in reducing the hydraulic conductivity (HC) of soils has been evaluated in several geotechnical engineering applications. However, optimizing MICP parameters to achieve minimal hydraulic conductivity for waste containment liners remains underexplored. This study presents a comprehensive laboratory analysis investigating the influence of bacterial suspension density and compaction energy on compacted lateritic soil, prepared under varying moisture conditions. Bacillus megaterium (B. megaterium) was introduced at different suspension densities, followed by compaction. Results revealed that increased bacterial density and compaction energy significantly reduced hydraulic conductivity due to calcite formation, confirmed through XRD, SEM, XRF, and FTIR analyses. To optimize the hydraulic conductivity, bio-inspired algorithms including particle swarm optimization (PSO), smell agent optimization (SAO), and bacterial foraging optimization (BFO) were deployed. Successive iterations demonstrated that PSO achieved the lowest hydraulic conductivity (k = 2.27 × 10−11 m/s), followed by SAO (k = 2.85 × 10−11 m/s) and BFO (k = 2.66 × 10−9 m/s). These findings highlight the critical role of compaction effort, moisture content, and bacterial density in designing compacted lateritic soil liners for geotechnical applications. Optimization results underscore PSO’s superior performance in achieving design criteria for liners.